1998
DOI: 10.1046/j.1365-2222.1998.00325.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of proteic allergens in refined peanut oil

Abstract: Allergic reactions to peanut oil are very much debated, even if the responsibility of peanut oil has been evoked in several cases of adverse reactions, including death related to severe asthma. The aim of the present study was to investigate the presence of allergenic proteins in peanut oil. Proteins were extracted from commercial refined peanut oil, with a relative content in the order of 0.1-0.2 microg per g of oil, and molecular sizes ranging from 14 up to 76kDa in SDS-PAGE. Eight protein bands were systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 39 publications
1
48
0
Order By: Relevance
“…However, refined peanut oil may contain sufficient peanut allergenic proteins to elicit a reaction in highly sensitive individuals (Olszewski et al, 1998). One of these proteins was recognised by IgE antibodies from a population of 11 peanut-allergic patients, four of whom reacted to commercially available refined peanut oils from the European market during a DBPCFC.…”
Section: Peanut Oilmentioning
confidence: 99%
“…However, refined peanut oil may contain sufficient peanut allergenic proteins to elicit a reaction in highly sensitive individuals (Olszewski et al, 1998). One of these proteins was recognised by IgE antibodies from a population of 11 peanut-allergic patients, four of whom reacted to commercially available refined peanut oils from the European market during a DBPCFC.…”
Section: Peanut Oilmentioning
confidence: 99%
“…However, they did not detect any protein in two other "cold pressed peanut oil" or in any of the three "hot-pressed peanut oils" tested. Olszewski et al (1998) using bicinchoninic protein acid assay revealed 3.4 µg/g of protein in "crude peanut oil" and 0.2 µg/g of protein in "neutralized peanut oil". They also tested six commercially available "refined peanut oil" and reported the protein content to be between 0.1-0.2 µg/g of oil.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…A total of 6 studies have addressed the immunochemical characterisation of the protein component of peanut oils (Nordlee et al, 1981;Hoffman et al, 1994;Teuber et al, 1997;Olszewski et al, 1998;Kull et al, 1999;Peeters et al, 2004 The applicant also states that there is no consensus on the most appropriate analytical methods for measurement of protein content of edible oils.…”
Section: In Vitro Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…2 It also mentioned an earlier study that demonstrated the persistence of small amounts of allergenic protein in peanut oil despite re nement. 3 Although the Committee on Safety of Medicines has determined that there is insuf cient evidence to conclude that exposure to topical medicines containletters to the editorsing peanut oil leads to sensitization to peanut protein, it has issued a precautionary recommendation that patients with known peanut allergy should avoid such medicines. Indeed, the labelling of these products is to be updated with new warnings.…”
mentioning
confidence: 99%